Emergence of Orientia tsutsugamushi as an important cause of Acute Encephalitis Syndrome in India. - Parul Jain; Shantanu Prakash; Piyush K Tripathi; Archana Chauhan; Shikha Gupta; Umesh Sharma; Anil K Jaiswal; Devraj Sharma; Amita Jain (Public Library of Science (PLoS), 2018)
Acute Encephalitis Syndrome (AES) is a major seasonal public health problem in Bihar, India. Despite efforts of the Bihar health department and the Government of India, burden and mortality of AES cases have not decreased, and definitive etiologies for the illness have yet to be identified.The present study was undertaken to study the specific etiology of AES in Bihar.Cerebrospinal fluid and/or serum samples from AES patients were collected and tested for various pathogens, including viruses and bacteria by ELISA and/or Real Time PCR.Of 540 enrolled patients, 33.3% (180) tested positive for at least one pathogen of which 23.3% were co-positive for more than one pathogen. Most samples were positive for scrub typhus IgM or PCR (25%), followed by IgM positivity for JEV (8.1%), WNV (6.8%), DV (6.1%), and ChikV (4.5%).M. tuberculosis and S. pneumoniae each was detected in ~ 1% cases. H. influenzae, adenovirus, Herpes Simplex Virus -1, enterovirus, and measles virus, each was detected occasionally. The presence of Scrub typhus was confirmed by PCR and sequencing. Bihar strains resembled Gilliam-like strains from Thailand, Combodia and Vietnam.The highlights of this pilot AES study were detection of an infectious etiology in one third of the AES cases, multiple etiologies, and emergence of O. tsutsugamushi infection as an important causative agent of AES in India.